2020
DOI: 10.1016/j.ijwd.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lichen sclerosus among women in the United States

Abstract: Background Vulvar lichen sclerosus (LS) is a chronic dermatosis for which the true prevalence is not well established. LS remains an underrecognized and undertreated disease, and treatment patterns and differences among various specialties that care for patients with LS are largely unknown. Objective This study sought to determine the prevalence of diagnosed vulvar LS, demographic characteristics, and diagnostic and treatment patterns in the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
0
14
1
6
Order By: Relevance
“…The worldwide prevalence of lichen sclerosus ranges from 0.1% to 1.67% [ 5 ]. Of note, the exact prevalence of VLS has not been established and is probably underestimated, particularly in young women [ 6 ]. Several papers report a bimodal onset of disease, that is, in prepubertal children and postmenopausal women [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide prevalence of lichen sclerosus ranges from 0.1% to 1.67% [ 5 ]. Of note, the exact prevalence of VLS has not been established and is probably underestimated, particularly in young women [ 6 ]. Several papers report a bimodal onset of disease, that is, in prepubertal children and postmenopausal women [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly develops in adults, occurring only in 0.3% of children [19]. The disease prevails in postmenopausal women, yet a moderate disease peak is observed in prepubertal children [20,21]. Due to a lack of large-scale epidemiological research comprising representative groups of people of all ages and both sexes, the exact LS prevalence is uncertain and seems to be underestimated.…”
mentioning
confidence: 99%
“…Due to a lack of large-scale epidemiological research comprising representative groups of people of all ages and both sexes, the exact LS prevalence is uncertain and seems to be underestimated. A few recent studies indicated that LS appears to be underdiagnosed, particularly in the young female population [20,22]. Most commonly, LS-induced lesions are localized in the anogenital area.…”
mentioning
confidence: 99%
See 2 more Smart Citations